Influence of Bavistin, Cefotaxime, Kanamycin and Silver Thiosulphate on Plant Regeneration of Mentha piperita (L.) – An Important Multipurpose Medicinal Plant - C.V.Naidu2*, P.Sujana1 and (Journal of Phytology, 2011)
Effect of different concentrations of bavistin, cefotaxime and kanamycin along wih the ethylene inhibitor STS were examined for in vitro plant regeneration using axillary bud explants of Mentha piperita. Filter sterilized bavistin, cefotaxime and kanamycin were added separately in the range of 0 – 300 mg (bavistin); 10, 20, 30, 40, 50, 100, or 120 µM/L (cefotaxime or kanamycin) to growth regulator free MS medium containing 3% sucrose. In a separate experiment bavistin (100 mg/l) along with growth regulators such as BAP and TDZ were added to MS medium containing 3% sucrose. Similarly the regeneration medium was supplemented with 10, 20, 30, 40, 50, 80, 100 or 120 µM/L of STS. Maximum number of shoots 6.85 ± 0.18 was seen with 150 mg/l bavistin with 100% regeneration. These plantlets were further maintained for root emergence on a rooting medium supplemented with growth regulators such as IAA, IBA and NAA. The rooted plants were acclimatized and transferred to field plots with 95% of plants surviving in the field.